Identifying ecological corridors for wetland waterbirds in Northeast China - Ping Zhang; Yueran Hu; Youming Quan; Qing Xu; Dehui Liu; Shaoyi Tian; Nian Chen (Ecological Indicators, 2022)
Ecological corridors have recently garnered increasing international attention as promising biodiversity conservation models to study the effects of climate change. However, very few studies have characterized waterbird ecological corridors and their responses to environmental variations. Here, a hybrid model approach combining the least resistance model and circuit theory was applied to identify ecological corridors for four kinds of waterbirds (Grus japonensis, Grus grus, Cygnus cygnus, Mergus squamatus) in Northeast China. This region contains many wetlands that are rich in waterbird species and are important habitats and breeding grounds for waterbirds on the East Asia-Australia migration route. Our findings demonstrated that the least cost routes of different waterbird species and their pinch points (i.e., areas exhibiting high waterbird transit and density) have the potential to become waterbird ecological corridors. However, we observed substantial differences in the number of least-cost paths and the structure and distribution of ecological corridor networks due to differences in the number and distribution of waterbird core habitat patches. The number and distribution of pinch points were also different. Over 85% of the waterbird occurrence points were not far from the least-cost routes or the pinch points, indicating that the detected least-cost routes and the pinch points were not only ecological corridors for waterbirds but also priority areas for the conservation of waterbird habitat networks. The methods proposed herein could thus be used as a basis for the identification of multi-species waterbird ecological corridors in other countries, as well as forest bird ecological corridors at other scales.